Polar Morphologies from First Principles: PbTiO3 Films on SrTiO3 Substrates and the p(2×Λ) Surface Reconstruction. Issue 11 (11th September 2020) - Baker, Jack S.; Bowler, David R.
Abstract: Low‐dimensional structures comprised of ferroelectric (FE) PbTiO3 (PTO) and quantum paraelectric SrTiO3 (STO) are hosts to complex polarization textures such as polar waves, flux‐closure domains, and polar skyrmion phases. Density functional theory (DFT) simulations can provide insight into this order, but are limited by the computational effort required. Within DFT, the novel multi‐site support function method is used to reduce the solution time for the electronic groundstate whilst preserving high accuracy. This allows for large‐scale simulations of PTO films on STO substrates with system sizes >2000 atoms. In the ultrathin limit, the polar wave texture with cylindrical chiral bubbles emerges as an intermediate phase between full‐flux‐closure domains and in‐plane polarization. This is driven by an internal bias field born of the compositionally broken inversion symmetry in the [001] direction. Manipulation of this built‐in field informs a new principle of design for control over chiral order on the nanoscale through the careful choice of substrate, surface termination, or use of overlayers. Antiferrodistortive (AFD) order locally interacts with these polar textures giving rise to strong FE/AFD coupling at the PbO terminated surface driving a p ( 2 × Λ ) surface reconstruction. This offers another pathway for the local control of ferroelectricity. Abstract : New insights into the control of ferroelectric textures on the nanoscale are provided using state‐of‐the‐art simulation methods. It is found that the inherent asymmetry in substrate/film systems drives a functional transition from ferroelectric stripe domains to a polar‐wave phase with chiral textures. Furthermore, local rotations of oxygen octahedra couple to polarization driving a new surface reconstruction.